ANALISIS KRIMINOLOGI TINDAKAN BRUTAL GENG MOTOR BERDASARKAN TEORI ASOSIASI DIFERENSIAL - Maulana Ruslan, Muhammad Ibnu; Rukman, Auliah Andika (Restorative Journal, 2024)
ABSTRACKThis research examines the brutal behavior of motorcycle gangs based on the perspective of differential association theory. The brutal behavior exhibited by members of motorcycle gangs is a social phenomenon that has become a serious concern in today's society. The brutal actions of motorcycle gangs encompass various crimes that lead to criminal prosecution. This phenomenon has a tangible impact on society as a whole.The study employs a normative juridical method by examining library materials or secondary data as the primary basis for research. This involves reviewing regulations and literature related to the issues being studied.The results indicate that the brutal behavior of motorcycle gangs, according to differential association theory, occurs due to two factors: 1. External Factors, and 2. Internal Factors. The brutal actions carried out by motorcycle gangs today are due to the perpetrators learning these brutal acts, which are categorized as crimes, as a result of interactions with crime, and this behavior is learned in various ways.Keywords: Motorcycle Gangs, Criminology, Differential Association Theory.